Antimicrobial action of α-arbutin, β-arbutin and hydroquinone: truth and fiction - Maslov, Oleksandr; Komisarenko , Mykola; Ponomarenko, Svitlana; Osolodchenko , Tetyana; Marchenko, Artem; Plis, Dmytro; Komisarenko , Andrey (Annals of Mechnikov's Institute, 2024)
Introduction. The leaves of lingonberry and bearberry are used in medicine for the treatment and prevention of urological infectious diseases due to the presence of diuretic and uroseptic action. This pharmacological activity is associated with the action of β-arbutin and hydroquinone. However, until now there has been no study of the relationship between the structure and antimicrobial action of β-arbutin and hydroquinone. The purpose of study was to estimate the antimicrobial action in vitro, in silico of α- and β-arbutin, hydroquinone, and also to conduct a comparative analysis of the antimicrobial properties of these compounds and to refute the theory of the presence of the antimicrobial action of arbutin only due to the action of hydroquinone.Materials and methods. Molecular docking was performed using AutoDockTools 1.5.6, antimicrobial activity was assessed using the "well" and "dilution" methods. Results and discussion. Theoretical studies have shown that α- and β-arbutin are highly selective inhibitors against gram-negative targets such as deoxyribonucleic acid (DNA) gyrase, dihydrofolate reductase (DHFR), deacetylase, and fungal targets such as 14α-demethylase, beta-1,3-glucanase, thymidylate kinase, whereas hydroquinone had low selectivity against all targets. The "well" assay showed that hydroquinone inhibits gram-positive bacteria more actively than β- and α-arbutin, and in the case of gram-negative bacteria, α-arbutin had a higher inhibitory effect than β-arbutin and hydroquinone, while β-arbutin inhibits fungal growth more actively than α-arbutin and hydroquinone. The minimum inhibitory concentration (MIC) values ​​of hydroquinone for gram-positive, gram-negative and fungal microorganisms were almost 2-3 times higher than MIC of β- and α-arbutin. Meanwhile, MIC of α-arbutin was lower for E. coli, P. vulgaris than β-arbutin, and the results were the same in other cases. Conclusions. The antimicrobial effect of α- and β-arbutin, hydroquinone against strains of S. aureus, B. subtilis, E. coli, P. vulgaris, P. aeruginosa and C. albicans was studied in vitro and in silico. Theoretical results showed that it is impossible to create a "panacea" from one compound that would suppress the growth of both bacteria and fungi. According to theoretical and practical results, the antimicrobial effect of α- and β-arbutin is 2-3 times higher than that of hydroquinone. It has been experimentally confirmed that α-arbutin suppresses the growth of gram-negative strains much more strongly than β-arbutin. The theory that arbutin has an antimicrobial effect only due to the action of hydroquinone has been theoretically and practically refuted. Keywords: hydroquinone, hydroquinone glycosides, structure-action relationship, comparative analysis, molecular docking